2022
DOI: 10.1186/s12934-022-01803-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of the recombinant Escherichia coli strain on defensins antimicrobial activity: BL21 versus Origami strain

Abstract: The growing emergence of microorganisms resistant to antibiotics has prompted the development of alternative antimicrobial therapies. Among them, the antimicrobial peptides produced by innate immunity, which are also known as host defense peptides (HDPs), hold great potential. They have been shown to exert activity against both Gram-positive and Gram-negative bacteria, including those resistant to antibiotics. These HDPs are classified into three categories: defensins, cathelicidins, and histatins. Traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…IBs are an active biomaterial that has already been explored in several applications such as cancer [ 73 ], biocatalysis [ 74 ], tissue regeneration [ 75 ] and immunostimulation [ 76 ], as they are highly stable protein nanoparticles with slow-release properties [ 56 , 57 , 77 ]. Recently, two studies have proven that HDP-based IBs are biologically active against different pathogenic bacteria [ 20 , 37 ]. In the first study, López-Cano et al showed that human α-defensin 5 (HD5) and lingual antimicrobial peptide (LAP) IBs are highly active against MRSA and Pseudomonas aeruginosa, with antimicrobial activities comparable to the soluble counterpart [ 37 ].…”
Section: Forms Of Recombinant Hdpsmentioning
confidence: 99%
See 4 more Smart Citations
“…IBs are an active biomaterial that has already been explored in several applications such as cancer [ 73 ], biocatalysis [ 74 ], tissue regeneration [ 75 ] and immunostimulation [ 76 ], as they are highly stable protein nanoparticles with slow-release properties [ 56 , 57 , 77 ]. Recently, two studies have proven that HDP-based IBs are biologically active against different pathogenic bacteria [ 20 , 37 ]. In the first study, López-Cano et al showed that human α-defensin 5 (HD5) and lingual antimicrobial peptide (LAP) IBs are highly active against MRSA and Pseudomonas aeruginosa, with antimicrobial activities comparable to the soluble counterpart [ 37 ].…”
Section: Forms Of Recombinant Hdpsmentioning
confidence: 99%
“…Recently, two studies have proven that HDP-based IBs are biologically active against different pathogenic bacteria [ 20 , 37 ]. In the first study, López-Cano et al showed that human α-defensin 5 (HD5) and lingual antimicrobial peptide (LAP) IBs are highly active against MRSA and Pseudomonas aeruginosa, with antimicrobial activities comparable to the soluble counterpart [ 37 ]. The second study showed the antibiofilm properties of IB-decorated surfaces against a carbapenem resistant Klebsiella pneumoniae [ 20 ], adding to the evidence that antimicrobial IBs can be effectively used against AMR bacteria.…”
Section: Forms Of Recombinant Hdpsmentioning
confidence: 99%
See 3 more Smart Citations